Enhancing University Education Through Project-Based Learning: A Case Study on Full Stack MEAN Development for Web Application Design and Development - Sirmoria, Deepika; Trupthi, M.; Vishnu Murthy, G (Journal of Engineering Education Transformations, 2025)
The aim of this paper is to design and develop the web application to support project based learning activities in “Web Programming in MEAN” course at Artificial Intelligence(AI), Anurag University(AU). Project-based learning (PBL) can be an effective strategy for developing twenty-first-century learning and skills in future-oriented settings under-graduate education. This technique allows students to conduct in-depth research on worthy themes, allowing them to learn from their experiences and apply their newly acquired information, skills, and attitudes to real-life situations. By using cutting-edge tools to build web applications, the system hopes to help students understand web application designing and programming.